Inorganic Graphenylene: A Porous Two-Dimensional Material With Tunable Band Gap - Perim, E.; Paupitz, R. [UNESP]; Autreto, P. A. S.; Galvao, D. S. (Amer Chemical Soc, 2014)
By means of ab initio calculations, we investigate the possibility of existence of a boron nitride (BN) porous two-dimensional nanosheet, which is geometrically similar to the carbon allotrope known as biphenylene carbon. The proposed structure, which we called inorganic graphenylene (IGP), is formed spontaneously after selective dehydrogenation of the porous boron nitride (BN) structure proposed by Ding et al. We study the structural and electronic properties of both porous BN and IGP, and it is shown that, by selective substitution of B and N atoms with carbon atoms in these structures, the band gap can be significantly reduced, changing their behavior from insulators to semiconductors, thus opening the possibility of band gap engineering for this class of two-dimensional materials.